Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Metode Implementasi Me - Muhammad Fikri Hidayattullah; Yustia Hapsari (Universitas Multimedia Nusantara, 2020)
One of the courses in D IV Informatics Engineering Department is Industrial Practices Work. This course is held to equip students of praxis in the world of software development. Unfortunately, so far the mechanism for implementing Industrial Practices Work is still in the conventional form. One of them is, for example, a student registers with the administration department of a study program, then requests a letter to be made to several software houses. In fact, sometimes the drafting of the request can be repeated in each group. This kind of process is very ineffective and slows down the performance of study programs. Therefore, through this research an information system was developed that could help to facilitate the implementation of Industrial Practices Work. The system development methodology used in this study is the waterfall method.